Fibrosarcoma with sarcomatosis and metastasis in a FeLV‐negative cat. (30th March 2020) - White, Mary E.; Yang, Ching; Hokamp, Jessica A.; Wellman, Maxey L.
Abstract: A 6‐year‐old, spayed female, mixed shorthair cat presented to the emergency service at The Ohio State University Veterinary Medical Center for evaluation of hypercalcemia, a right eye mass, and multiple intrathoracic and intra‐abdominal masses. Cytologic evaluation of one of the abdominal masses revealed a uniform population of large, anaplastic mesenchymal cells found individually, in loose aggregates, and occasionally associated with pink, extracellular matrix. The cytology was consistent with a malignant mesenchymal neoplasm, with primary consideration given to fibrosarcoma and hemangiosarcoma. The cat was euthanized and histopathology confirmed disseminated fibrosarcoma. Fibrosarcoma comprises 12%‐41% of feline cutaneous tumors and affects cats at a mean age of 9.6 years. Three manifestations of fibrosarcoma predominate in cats: spontaneous solitary fibrosarcoma, vaccine‐induced/injection site fibrosarcoma, and oncogene‐induced (FSV) fibrosarcoma. The history, signalment, and results from diagnostics performed did not support solitary fibrosarcoma or injection‐induced sarcoma. Although some criteria fit with virally induced fibrosarcoma, such as age and the presence of multiple fibrosarcomas, the neoplastic population was negative for FeLV IHC. The presence of fibrosarcomas throughout the pleural and peritoneal cavity was most compatible with sarcomatosis and the distant metastasis of an unidentified primary neoplasm. To the authors' knowledge, this is the first reported case of sarcomatosis in a FeLV‐negative cat.